Quality of Life of Patients undergong Haemodialysis at B.P. Koirala Institute of Health Sciences - Anu, VK; Pushpa, Parajuli; Kumar, Sharma Sanjib (Journal of Manmohan Memorial Institute of Health Sciences, 2014)
DOI: http://dx.doi.org/10.3126/jmmihs.v1i2.9904 Journal of Manmohan Memorial Institute of Health Sciences Vol.1(2) 2013; 19-25